2016
DOI: 10.29044/v7i1p19
|View full text |Cite
|
Sign up to set email alerts
|

TA Treatment of Depression: A Hermeneutic Single-Case Efficacy Design Study - ‘Penelope’

Abstract: This study is the second of a series of three, and represents an Italian replication of a previous UK -based case series (Widdowson 2012a(Widdowson , 2012b(Widdowson , 2012c(Widdowson , 2013

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Benelli and colleagues, with Widdowson himself acting as a consultant to confirm that the studies were accurate replications, provided three more cases within Italy (Benelli et al 2016a(Benelli et al , 2016b(Benelli et al , 2016c. At that time, and for the cases in this issue, the practitioners were able to base their work on Widdowson's (2015) published treatment manual.…”
Section: Editorial Julie Haymentioning
confidence: 95%
“…Benelli and colleagues, with Widdowson himself acting as a consultant to confirm that the studies were accurate replications, provided three more cases within Italy (Benelli et al 2016a(Benelli et al , 2016b(Benelli et al , 2016c. At that time, and for the cases in this issue, the practitioners were able to base their work on Widdowson's (2015) published treatment manual.…”
Section: Editorial Julie Haymentioning
confidence: 95%
“…Recently, several HSCEDs supporting the effectiveness of TA treatment for depression (Widdowson, 2012a(Widdowson, , 2012b(Widdowson, , 2012c(Widdowson, , 2013Benelli, 2016aBenelli, , 2016bBenelli, , 2016c have been published, as was an additional adjudicated study which demonstrated effectiveness of TA for mixed depression and anxiety (Widdowson, 2014). Furthermore, a related study was published on TA for emetophobia (Kerr, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This study is the first of a series of seven, and belongs to the second Italian systematic replication of findings from two previous case series (Widdowson 2012a(Widdowson , 2012b(Widdowson , 2012c(Widdowson , 2013Benelli, 2016aBenelli, , 2016bBenelli, , 2016c and was conducted under the auspices of the European Association for Transactional Analysis (EATA) and the University of Padua.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…
AbstractThis study is the third of a series of seven, and belongs to the second Italian systematic replication of findings from two previous series (Widdowson 2012a(Widdowson , 2012b(Widdowson , 2012c(Widdowson , 2013Benelli, 2016aBenelli, , 2016bBenelli, , 2016c) that investigated the effectiveness of a manualised transactional analysis treatment for depression through Hermeneutic Single-Case Efficacy Design (HSCED). Major Depression and Subthreshold Depression are often in comorbidity with Anxiety disorders in childhood and adolescence and represent a risk factor for ongoing mental health problems in adulthood.
…”
mentioning
confidence: 99%